From Farm to Fork: Streptococcus suis as a Model for the Development of Novel Phage-Based Biocontrol Agents - Emmanuel Kuffour Osei; Jennifer Mahony; John G. Kenny (Viruses, 2022)
Bacterial infections of livestock threaten the sustainability of agriculture and public health through production losses and contamination of food products. While prophylactic and therapeutic application of antibiotics has been successful in managing such infections, the evolution and spread of antibiotic-resistant strains along the food chain and in the environment necessitates the development of alternative or adjunct preventive and/or therapeutic strategies. Additionally, the growing consumer preference for “greener” antibiotic-free food products has reinforced the need for novel and safer approaches to controlling bacterial infections. The use of bacteriophages (phages), which can target and kill bacteria, are increasingly considered as a suitable measure to reduce bacterial infections and contamination in the food industry. This review primarily elaborates on the recent veterinary applications of phages and discusses their merits and limitations. Furthermore, using Streptococcus suis as a model, we describe the prevalence of prophages and the anti-viral defence arsenal in the genome of the pathogen as a means to define the genetic building blocks that are available for the (synthetic) development of phage-based treatments. The data and approach described herein may provide a framework for the development of therapeutics against an array of bacterial pathogens.